OPTIMALISASI PENDAPATAN ASLI DESA MELALUI EDUKASI PENGELOLAAN POTENSI EKONOMI DESA DI DESA PULAU RAJAK KABUPATEN BANYUASIN - Enni Merita; Kinaria Afriani; Warmiyana ZA; Putri Sari Nilam Cayo; Tobi Haryadi; Husnaini (Sumpah Pemuda : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program was conducted to improve the understanding of the village government, MSME actors, and the community of Pulau Rajak Village, Banyuasin Regency, regarding the importance of managing village economic potential as a source of Village Original Revenue. Villages have the authority to manage their resources and assets to support development and improve community welfare. However, in practice, village economic potential has not always been identified and managed optimally as a source of village revenue. This program aims to provide education on the sources of Village Original Revenue, mapping of village economic potential, the role of village-owned enterprises, utilization of village assets, and strategies for managing local MSMEs as part of strengthening the village economy. The methods used include counseling, interactive discussion, village potential mapping, and evaluation of participants’ understanding. The results show an increase in participants’ understanding of the importance of planned, transparent, and accountable management of village economic potential. This program is expected to encourage the Pulau Rajak Village Government to develop sustainable village economic policies oriented toward increasing Village Original Revenue.